Online Media Surveillance: Coverage of Meningitis Outbreaks in Ghana - Smith, M.S.; Tietaah, G.K.M. (Athens Journal of Health, 2017)
This study explores the nature of reportage on meningitis outbreaks in Ghana by two online media outlets, graphiconline and myjoyonline. Specifically, the study was designed to explore the news frames, level of prominence, sources of information and surveillance function performed by the media during an infectious disease outbreak. Framing was the main theoretical framework that guided the study. The content analysis method was employed to assess a total of 60 published news articles during a four-month period, December 1, 2015 to March 31, 2016. The findings revealed that "action" and "consequence" were the major frames the media used to report on meningitis outbreaks. Stories about the meningitis health crisis in Ghana were not displayed prominently online. Although the web publications generally promote multimedia content, few videos, podcasts, photos or online polls were utilized. In terms of sourcing, the online meningitis stories featured mostly government representatives and health officials and did little to engage residents and communities affected. The online media also failed to fulfill their surveillance function of reporting on trends and alerting the public of severity of the outbreak in Ghana. Given the findings, it is suggested that journalists interested in health reporting such as the meningitis outbreak receive extensive media training in order to report trends and perform their surveillance role.
Research Article
Keywords: Framing; Ghana; Meningitis